Borcs6 is required for endo‐lysosomal degradation during early development. Issue 8 (21st June 2022) - Bell, Charlotte J.; Gupta, Neha; Tremblay, Kimberly D.; Mager, Jesse
Abstract: Early development and differentiation require precise control of cellular functions. Lysosomal degradation is a critical component of normal cellular homeostasis, allowing for degradation of signaling molecules, proteins, and other macromolecules for cellular remodeling and signaling. Little is known about the role of lysosomal function in mammalian embryos before gastrulation. Borcs6 is a protein involved in lysosomal trafficking as well as endo‐lysosomal and autophagosome fusion. Here, we show that Borcs6 is necessary for efficient endo‐lysosomal degradation in the early embryo. Although embryos lacking Borcs6 are developmentally comparable to control littermates at E5.5, they are characterized by large cells containing increased levels of late endosomes and abnormal nuclei. Furthermore, these embryos display a skewed ratio of extraembryonic and embryonic cell lineages, are delayed by E6.5, and do not undergo normal gastrulation. These results demonstrate the essential functions of lysosomal positioning and fusion with endosomes during early embryonic development and indicate that the early lethality of BORCS6 mutant embryos is primarily due to defects in the HOPS‐related function of BORC rather than lysosomal positioning.